DNA ploidy pattern of each carcinomatous component in adenosquamous lung carcinoma - Ichinose, Yukito; Hara, Nobuytiki; Takamori, Shinzo; Maeda, Kazunobu; Yano, Tokujiro; Ohta, Mitsuo (The Annals of thoracic surgery, 1993)
The relationship between adenocarcinomatous and squamous carcinomatous components in 12 surgically resected adenosquamous lung carcinomas was analyzed using DNA flow cytometry. Well-preserved parts of the tumor showing either adenocarcinoma or squamous cell carcinoma were identified on paraffin blocks. The cells obtained from each component were stained with propidium iodide for DNA flow cytometry. In the analysis of DNA flow cytometry, both components in the same tumor were defined as being related to each other when they showed diploidy or when at least one DNA index of abnormal clones between two aneuploid components was identical. According to these criteria, 8 (67%) of the 12 tumors showed a relationship between adenocarcinomatous and squamous carcinomatous components. This suggests that, despite the different phenotypes, both components of some adenosquamous lung carcinomas may share similar biological characteristics.